Exploring the creative possibility of a hybrid design thinking workshop through finding solutions for children’s safety in the childcare environment - Lee, Hyun-Kyung; Kim, Min Kyong; Lee, Minji (Creativity Studies, 2023)
Design thinking process has two ways of on and off-line. In the online method, it facilitates communication more freely through the setting of anonymity, while the offline method allows participants to understand the comprehensive context of the workshop. This study investigates the creative possibility of a hybrid design thinking process through a workshop using “camera-off ”: anonymous setting, “camera-on”: open setting, and instant visualization to find solutions for children’s safety in the childcare environment. In the methodology, a qualitative method of three-dimensional interviews and observations were used to collect the active participants’ opinions, and then the content analysis and the descriptive analysis were conducted. Three major childcare-related problems were noted during the workshop observations: 1) safety issues from children’s physical activities; 2) teachers’ excessive stress in childcare facilities, and 3) communication problems between parents and teachers. It was suggested that creative smart devices and artificial intelligence technologies could be helpful to relieve these problems. In insights of the hybrid design thinking workshop, the following points were noted: 1) active participants could freely share ideas in anonymous setting with “camera-off”; 2) active participants could understand various desires of diverse fields with “camera-on”, and 3) active participants could understand find core problems and solutions through instant visualization. Hybrid design thinking is an creative method for understanding problems and finding solutions.